The Policy Implementation Of Social Ministry’s Cash Assistance Program During The Covid-19 Pandemic In Jakarta - Rulandari, Novianita; Natision, Alian; Esien, Eddy Bruno; Kesmawan, Andri Putra (Universitas Muhammadiyah Yogyakarta, 2022)
The Ministry of Social’s Cash Social Assistance Policy is one of the Government’s programs to maintain the purchasing power of people directly affected by the COVID-19 pandemic. The purpose of this study is to analyze and evaluate the implementation of cash social assistance policies during the COVID-19 pandemic, analyze the factors that hinder the successful implementation of cash social assistance policies during the COVID-19 pandemic, and analyze the factors that support the social assistance policies during the COVID-19 pandemic. The research method used was descriptive qualitative. Informants in this study were bureaucrats, policy implementers, and the community as beneficiaries. This study found non-compliance with policy implementers in the standard and policy targets by deliberately violating them for certain benefits. Factors inhibiting cash assistance policy implementation include ineffective and inefficient policy output to target intended beneficiaries, lack of recipient’s name in the Integrated Social Welfare Data (DTKS), inaccurate redistribution of social assistance benefits, and inappropriate use of social assistance funds to purchase non-basic needs. Supporting factors are strict government supervision and evaluation monitoring on the use of social assistance funds that may reduce cash transfer and impair intended beneficiaries’ access to scarce resources in times of contemporary COVID-19 pandemic crisis-related society.